Treatment of dry eye disease in traditional Persian medicine: A narrative review - Ebrahim Salimi-Sabour; Seyed Mohammad Zarei (Shahrekord University of Medical Sciences, 2022)
Background and aims: Dry eye disease (DED) is a globally prevalent disorder due to the loss of homeostasis of the tear film that causes a range of different signs and symptoms. This problem affects visual function and patients' daily activities and damages physical and psychological health and finally the quality of life while it has no definite cure until now. Thus, developing new medicines and formulations is needed. Meanwhile, traditional Persian medicine as an ancient comprehensive school among the world's traditional medicine is a good source of active ingredients and formulations. Methods: Prescribed herbal medicines and related formulations for DED in traditional Persian medicine references including Exir-e-Azam, Tebb-e-Akbari, Moalejat-e-Aghili, and Makhzan-al-Advieh were investigated and analyzed in comparison with recent therapeutic studies. Results: Our findings show that traditional Persian medicine scientists relied on mucilage-containing materials like psyllium and quince seeds and unsaturated and polyunsaturated plant oils such as sweet almond oil, pumpkin seed oil, and olive oil as principal components for treating DED. Conclusion: DED treatment in Persian traditional medicine was based on using mucilages and plant oils mainly as ophthalmic drops to keep moisture and lubricate eyelid movement. Moreover, advised medicines were generally in accordance with modern medicine findings and found to have antioxidant, anti-inflammatory, and immunomodulatory activities that can beneficially modulate pathological mechanisms of dry eye disease.